TREND AND RECOVERY OF NON-PERFORMING ASSETS IN INDIAN BANKING SECTOR - BHAGYALAKSHMI.G (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The banking system of an economy is foremost importance for its financial and economic development .It forms the core of the financial sector and plays a critical role in transmitting monetary policy impulses to entire economic system .Hence the stability of banking sector is paramount importance for the development of an economy .An important indicator today that determines the solidity of the banks are the Non Performing Asset(NPA) Many banks are facing the problem of NPAs which not limited only to the banks but it is posing a hazardous threat to the overall economy. The threat is across the various sectors, and the Indian economy is very alarming. It is necessary to trim down the NPAs to improve the financial health in banking system. An attempt has been made in this paper to understand NPAs, factors contributing to NPA, trend & recovery of NPA through various channels